Capture rate consequences of multispherule aggregate formation in gases—combined roles of direct interception and interspherule momentum "shielding". Issue 7 (3rd July 2018) - Rosner, Daniel E.; Tandon, Pushkar
ABSTRACT: Our recent work on the consequences of multispherule cluster aggregate (CA) formation and deposition-rates on much larger solid targets has emphasized the decisive role of "momentum-shielding" in determining aggregate "mobility" compared to N isolated spherules in the same gaseous environment—an effect analogous to the drag-reduction advantages experienced by birds electing to move "in formation." The extent of "momentum shielding" is conveniently quantified via a dimensionless function: Smom (N;Kn1, aggregate structure), which facilitates predicting the deposition-rate consequences of aggregation in aerosol flow systems when the cluster deposition mechanism is dominated by either: (i) isothermal convective-diffusion (C-D), (ii) thermophoresis (T-P) or: (iii) inertial impaction (I-I). Significantly, isothermal C-D was found to be the only transport-mechanism leading to aggregation-induced reductions in spherule deposition rates on large targets (cf. isolated spherules present at the same mainstream spherule volume fraction). However, we demonstrate here that, for aggregate deposition on sufficiently small solid targets—e.g., fibrous filter elements with diameters of O(10 μm)—even these reductions, which exceed one decade for N = O(10 3 ), can be overcome by the mechanism of "direct-interception" (D-I) associated with nonzero effective aggregate size, without the need to invoke either inertial impaction or thermophoresis. This is especially true for Diffusion-Limited (i.e., "open") CAs (with Df = 1.8) at gas pressures such that the constituent spherules are near the continuum (Kn1 << 1) limit. Our present analysis and numerical illustrations exploit the fact that direct-interception is expected to play a negligible role for the capture of individual (dense) nanospherules (perhaps comparable in size to the prevailing gas molecule mean-free-path) but the underlying theory, exploited, extended, and illustrated here, was developed with the help of initial capture rate experimental data for much larger diameter (but unaggregated) aerosols on single filter fibers in low Re crossflow. With such small diameter targets, we demonstrate that this "interception" augmentation for large CAs can occur even for the limiting case of rcp Df = 3 aggregates, before the expected onset of CA-inertial effects–i.e., StkN << Stkcrit, where, for Re = O(1), Stkcrit is also O(1). A simple method is also presented for predicting interception-modified spherule deposition rates in the presence of log-normal type aggregate size distributions. Copyright © 2018 American Association for Aerosol Research